RETRACTED: The Heart of Silk Road “Xinjiang,” Its Genetic Portray, and Forensic Parameters Inferred From Autosomal STRs - Adnan, Atif; Anwar, Adeel; Simayijiang, Halimureti; Farrukh, Noor; Hadi, Sibte; Wang, Chuan-Chao; Xuan, Jin-Feng (Frontiers in Genetics, 2021)
The Xinjiang Uyghur Autonomous Region of China (XUARC) harbors almost 50 ethnic groups including the Uyghur (UGR: 45.84%), Han (HAN: 40.48%), Kazakh (KZK: 6.50%), Hui (HUI: 4.51%), Kyrgyz (KGZ: 0.86%), Mongol (MGL: 0.81%), Manchu (MCH: 0.11%), Uzbek (UZK: 0.066%) and so on, which make it one of the most colorful regions with abundant cultural and genetic diversities. In our previous study, we established allelic frequency databases for 14 autosomal short tandem repeats (STRs) for four minority populations from XUARC (MCH, KGZ, MGL, and UZK) using AmpFlSTR® Identifiler PCR amplification kit. In this study, we genotyped 2121 samples using GoldenEyeTM 20A kit (Beijing PeopleSpot Inc.) amplifying 19 autosomal STR loci for four major ethnic groups (UGR, HAN, KZK & HUI). These groups make up 97.33% of the total XUARC population. The total number of alleles for all the 19 STRs in these populations ranged from 232 (HAN) to 224 (KZK). We did not observe any departures from Hardy–Weinberg equilibrium (HWE) in these populations after sequential Bonferroni correction. We did find minimal departure from linkage equilibrium (LE) for a small number of pairwise combinations of loci. The match probabilities for the different populations ranged from 1 in 1.66 x 1023 (HAN) to 6.05 x 1024 (HUI), the combined power of exclusion ranged from 0.999 999 988 (HUI) to 0.999 999 993 (UGR), and the combined power of discrimination ranged from 0.999 999 999 999 999 999 999 983 (HAN) to 0.999 999 999 999 999 999 999 997 (UGR). Genetic distances, principal component analysis (PCA), STRUCTURE analysis, and the phylogenetic tree showed that genetic affinity among studied populations is consistent with linguistic, ethnic, and geographical classifications.